Neonatal axillary hidradenitis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2014)
Case report. A 15-day-old baby girl first arrived to our observation because the mother during the bath had noticed a small lesion in the right axillary region that after 2 days had eroded with leakage of yellow, turbid fluid. The baby girl was born at term by natural delivery after a pregnancy complicated by minimum placental detachment in the 20th week. The physical examination showed a physiological scaling of the newborn, bilateral breast swelling and in the right axillary region a cylindrical dermal nodule, 10 mm long and 4 mm wide, hard-elastic, painless and movable on the deep layers (Fig. 1). We diagnosed axillary hidradenitis and prescribed topical fusidic acid 3 times per day until the regression. The lesion regressed completely in a week without leaving outcomes. 3 months later there were not recurrences.